Preparation method and application of sulfur-cadmium-zinc-copper-based composite photocatalyst

By combining one-dimensional CuZnCdS with two-dimensional Ti3C2 MXene, a sulfhydryl-cadmium-zinc-copper-based composite photocatalyst was prepared, which solved the problem of low efficiency of existing photocatalysts in the process of photocatalytic water splitting and hydrogen production, and achieved efficient photocatalytic decomposition of water to prepare hydrogen.

CN119771456APending Publication Date: 2025-04-08JIANGSU SOPO CHEM +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510060939.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the process of photocatalytic water splitting and hydrogen production, existing semiconductor photocatalysts have problems such as low photogenerated carrier separation efficiency, limited solar absorption range, and small number of active sites, resulting in low energy conversion efficiency.

Method used

By combining the one-dimensional quaternary metal sulfide CuZnCdS with two-dimensional Ti3C2 MXene, a sulfhydryl-cadmium-zinc-based composite photocatalyst is prepared to effectively inhibit the recombination of photogenerated carriers and accelerate the separation and transmission of photogenerated carriers.

Benefits of technology

The photocatalytic activity and stability of the photocatalyst is improved, and the efficiency of photocatalytic decomposition of water is enhanced to prepare hydrogen. It is simple to operate and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771456A_ABST
    Figure CN119771456A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a sulfur-cadmium-zinc-copper-based composite photocatalyst, which comprises the following steps: adding zinc acetate dihydrate, cadmium acetate dihydrate and copper nitrate trihydrate into deionized water, uniformly mixing, adding sodium sulfide nonahydrate, stirring and dissolving, adding titanium carbide, uniformly mixing to obtain a mixed solution, and drying to obtain the sulfur-cadmium-zinc-copper-based composite photocatalyst. Transferring the mixed solution into a stainless steel reaction kettle with a polytetrafluoroethylene lining, then putting the stainless steel reaction kettle into a drying oven for reaction, after the reaction is finished, centrifugally washing a reaction product, collecting a solid product, and drying to obtain a finished product. The one-dimensional quaternary metal sulfide CuZnCdS and the two-dimensional Ti3C2MXene are compounded, compounding of photon-generated carriers can be effectively inhibited, separation and transmission of the photon-generated carriers are accelerated, compared with an existing method, the method is easy to operate and low in cost, and the prepared photocatalyst material has excellent photocatalytic activity and is particularly suitable for preparing hydrogen through photocatalytic decomposition of water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of using photocatalytic materials, and specifically relates to a preparation method and application of a sulfur-cadmium-zinc-copper based composite photocatalyst. Background Art

[0002] As global energy demand continues to grow, how to meet the growing energy demand has become a major challenge facing the world. Hydrogen energy has become one of the best alternative energy sources to traditional fossil energy due to its wide distribution, high combustion calorific value, and pollution-free combustion. Using photocatalysts to split water under visible light to produce hydrogen is a promising method for converting solar energy into hydrogen energy. However, early semiconductor photocatalysts had problems such as low efficiency in separating photogenerated carriers, limited solar absorption range, and a small number of active sites, which resulted in low energy conversion efficiency and greatly limited their application.

[0003] Excellent photocatalysts should have appropriate band gaps, excellent solar absorption, favorable energy band levels, and efficient charge separation, thereby generating more photoinduced electrons and holes for redox reactions. Researchers have found that sulfides have excellent photocatalytic properties, especially multimetallic sulfides (such as ZnIn2S4, Zn x Cd 1-x S, etc.). Due to the synergistic effect of sufficient reduction potential between the two metal ions, they can exhibit excellent and stable hydrogen evolution reaction (HER) characteristics during continuous photocatalysis. Quaternary sulfides can be used to evaluate special photocatalytic activities, so they are more useful in research. Among them, 1D CuZnCdS (CZCS) exhibits excellent photocatalytic performance due to its environmental friendliness, adjustable band gap, good thermal and chemical stability, and easy synthesis from resource-rich and inexpensive precursors. It can be used as a photocatalytic unit while effectively producing hydrogen from water. However, when this one-dimensional metal sulfide is used as a photocatalyst, its photogenerated carrier recombination velocity is fast during photoexcitation, and its photoresponsiveness to visible light is insufficient. In addition, its photoreaction stability is poor.

[0004] Studies have shown that the contact between the interfaces of photogenerated carriers can be improved through the catalytic recombination, which can inhibit the recombination of carriers and effectively promote the transmission of photogenerated carriers. At present, the materials commonly used as catalytic recombination mainly include precious metals (Pt, Au, Pd, etc.), metal sulfides (MoS2, WS2, etc.), graphene, carbon nanotubes, etc. However, precious metal materials have the problem of high cost, while materials such as metal sulfides, graphene, and carbon nanotubes have poor conductivity, and the effect of promoting the transmission of photogenerated carriers is not ideal.

[0005] MXenes are an emerging class of two-dimensional (2D) materials composed of two-dimensional (2D) transition metal carbides and nitrides, synthesized by selectively etching the A layer (third or fourth group elements) of the corresponding MAX phase. n+1 X n T x , where M is a transition metal, such as Ti, Ta, Cr, etc., and X is carbon or nitrogen. To date, researchers have successfully prepared nearly 30 different MXenes, and have theoretically predicted the configurations and corresponding properties of some MXenes using methods such as density functional theory (DFT). According to research reports, MXenes such as Ti2C, Ti3C2, Ta4C3, Ti3CN, TiNbC, and TiCr2C2 have been used. Among them, two-dimensional Ti3C2 MXene has been widely studied as a catalyst for the reduction of CO2, H2O, and Cr(VI) due to its large specific surface area and excellent metallic conductivity. At present, there is no research report on the preparation of photocatalysts by combining 1D CuZnCdS (CZCS) with two-dimensional Ti3C2 MXene. Summary of the invention

[0006] The purpose of the present invention is to solve the deficiencies of the above-mentioned prior art and provide a method for preparing a sulfur-cadmium-zinc-copper based composite photocatalyst. The method is simple to operate and low in cost. The prepared photocatalyst has excellent photocatalytic activity and excellent stability.

[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0008] A method for preparing a sulfur-cadmium-zinc-copper based composite photocatalyst comprises the following steps:

[0009] (1) adding zinc acetate dihydrate, cadmium acetate dihydrate, and copper nitrate trihydrate to deionized water, mixing them evenly, adding sodium sulfide nonahydrate and stirring to dissolve, and then adding titanium carbide and mixing them evenly to obtain a mixed solution;

[0010] (2) The mixed solution obtained in step (1) is transferred into a stainless steel reactor with a polytetrafluoroethylene liner, and then placed in an oven for reaction. After the reaction is completed, the reaction product is centrifuged and washed, and the solid product is collected and dried to obtain a sulfur-cadmium-zinc-copper based composite photocatalyst.

[0011] Furthermore, in step (1), the mass ratio of zinc acetate dihydrate, cadmium acetate dihydrate, copper nitrate trihydrate, sodium sulfide nonahydrate and titanium carbide is (0.05-1): (0.1-1.5): (0.01-0.2): (0.4-1): (0.01-0.3).

[0012] Furthermore, in step (2), the reaction temperature is 140-180° C. and the reaction time is 2-6 hours.

[0013] Furthermore, in step (2), the number of centrifugal washing is 2 to 4 times.

[0014] Furthermore, in step (2), the drying temperature is 60 to 70° C., and the drying time is 10 to 20 hours.

[0015] The application of the sulfur-cadmium-zinc-copper based composite photocatalyst prepared by the above method in photocatalytic decomposition of water to produce hydrogen.

[0016] Beneficial effects of the invention: The invention discloses a method for preparing a sulfur-cadmium-zinc-copper based composite photocatalyst, which can effectively inhibit the recombination of photogenerated carriers and accelerate the separation and transmission of photogenerated carriers by combining one-dimensional quaternary metal sulfide CuZnCdS with two-dimensional Ti3C2 MXene. The method of the invention is simple to operate and low in cost. The prepared photocatalyst material has excellent photocatalytic activity and is particularly suitable for photocatalytic decomposition of water to produce hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 XRD pattern of 1D / 2D CZCS / TC prepared in Example 2;

[0018] Figure 2 The scanning electron microscope image and EDS elemental analysis image of the 1D / 2D CZCS / TC prepared in Example 2;

[0019] Figure 3 X-ray photoelectron spectrum of 1D / 2D CZCS / TC prepared in Example 2;

[0020] Figure 4 UV-visible diffuse reflectance spectrum and band structure of 1D / 2D CZCS / TC prepared in Example 2;

[0021] Figure 5 Electrochemical impedance spectroscopy, transient photocurrent, photoluminescence spectrum and time-resolved photoluminescence spectrum of 1D / 2D CZCS / TC prepared in Example 2;

[0022] Figure 6 These are the photocatalytic performance, apparent quantum efficiency and stability test results of the 1D / 2D CZCS / TC prepared in Example 2. DETAILED DESCRIPTION

[0023] The technical solution of the present invention is clearly and completely described below in conjunction with the accompanying drawings and specific embodiments.

[0024] Comparative Example 1

[0025] Preparation of 1D CuZnCdS nanoparticles:

[0026] 0.137 g zinc acetate dihydrate, 0.167 g cadmium acetate dihydrate, and 0.0274 g copper nitrate trihydrate were added to 30 mL deionized water, and dissolved by ultrasonic and stirring at room temperature for 10 min. Then, 0.48 g sodium sulfide nonahydrate was added, and dissolved by ultrasonic and stirring for 1 h to obtain a mixed solution. The mixed solution was transferred into a stainless steel reactor with a polytetrafluoroethylene liner, and heated in an oven set at 140°C for reaction for 2 h. After the reaction, the obtained solution was centrifuged and washed twice with deionized water (10000 rpm, 1 min), and the solid product was collected and dried at 60°C for 12 h to obtain cadmium zinc copper sulfide nanoparticles, which were recorded as 1D CuZnCdS.

[0027] Comparative Example 2

[0028] Preparation of 2D Ti3C2:

[0029] Put 10mL of 40% HF solution into a polytetrafluoroethylene beaker, then put in 1g Ti3AlC2, stir for 24 hours (temperature 35°C, 300rpm), then put the solution into a 50mL centrifuge tube for washing, then add deionized water until 50mL, centrifuge and wash at 3500rpm for 2min, repeat the washing with deionized water until the pH of the solution is 7, finally, wash with ethanol, and further centrifuge the solution at 3500rpm to obtain 2D Ti3C2.

[0030] Example 1

[0031] A method for preparing a sulfur-cadmium-zinc-copper based composite photocatalyst comprises the following steps:

[0032] (1) 0.137 g of zinc acetate dihydrate, 0.167 g of cadmium acetate dihydrate, and 0.0274 g of copper nitrate trihydrate were added to 30 mL of deionized water, and dissolved by ultrasonication and stirring at room temperature for 10 min. Then, 0.48 g of sodium sulfide nonahydrate was added and dissolved by ultrasonication and stirring for 0.5 h. Then, 0.02 g of titanium carbide was added and dissolved by ultrasonication and stirring for 1 h to obtain a mixed solution.

[0033] (2) The mixed solution obtained in step (1) was transferred into a stainless steel reactor with a polytetrafluoroethylene liner, and then placed in an oven at 140° C. for heating reaction for 2 h. After the reaction was completed, the reaction product was centrifuged and washed twice with deionized water (10,000 rpm, 1 min), and the solid product was collected and dried at 60° C. for 12 h to obtain a sulfur-cadmium-zinc-copper-based composite photocatalyst, which was recorded as 1D / 2D CZCS / TC.

[0034] Example 2

[0035] A method for preparing a sulfur-cadmium-zinc-copper based composite photocatalyst comprises the following steps:

[0036] (1) 0.274 g of zinc acetate dihydrate, 0.333 g of cadmium acetate dihydrate, and 0.0548 g of copper nitrate trihydrate were added to 50 mL of deionized water, and dissolved by ultrasonication and stirring at room temperature for 20 min. Then, 0.72 g of sodium sulfide nonahydrate was added and dissolved by ultrasonication and stirring for 1 h. Then, 0.04 g of titanium carbide was added and dissolved by ultrasonication and stirring for 2 h to obtain a mixed solution.

[0037] (2) The mixed solution obtained in step (1) was transferred into a stainless steel reactor with a polytetrafluoroethylene liner, and then placed in an oven at 160° C. for heating and reaction for 4 h. After the reaction was completed, the reaction product was centrifuged and washed three times with deionized water (10,000 rpm, 1 min), and the solid product was collected and dried at 60° C. for 12 h to obtain a sulfur-cadmium-zinc-copper-based composite photocatalyst, which was recorded as 1D / 2D CZCS / TC.

[0038] Example 3

[0039] A method for preparing a sulfur-cadmium-zinc-copper based composite photocatalyst comprises the following steps:

[0040] (1) 1.00 g of zinc acetate dihydrate, 1.5 g of cadmium acetate dihydrate, and 0.2 g of copper nitrate trihydrate were added to 60 mL of deionized water, and dissolved by ultrasonication and stirring at room temperature for 30 min. Then, 1 g of sodium sulfide nonahydrate was added and dissolved by ultrasonication and stirring for 1 h. Then, 0.3 g of titanium carbide was added, and ultrasonication and stirring were performed for 3 h to obtain a mixed solution.

[0041] (2) The mixed solution obtained in step (1) was transferred into a stainless steel reactor with a polytetrafluoroethylene liner, and then placed in an oven at 180° C. for heating reaction for 6 h. After the reaction was completed, the reaction product was centrifuged and washed 4 times with deionized water (10,000 rpm, 1 min), and the solid product was collected and dried at 60° C. for 12 h to obtain a sulfur-cadmium-zinc-copper-based composite photocatalyst, which was recorded as 1D / 2D CZCS / TC.

[0042] Figure 1 The XRD pattern of 1D / 2D CZCS / TC prepared in Example 2 shows that pure 1D CuZnCdS nanoparticles show three main diffraction peaks at 27.34°, 45.32° and 53.66°, corresponding to (111), (220) and (311) planes, respectively. In addition, XRD also proves the presence of tungsten pyroxene phase and sphalerite phase in one-dimensional CuZnCdS. The 1D / 2D CuZnCdS / Ti3C2 composite photocatalyst shows typical diffraction peaks consistent with 1D CuZnCdS and 2D Ti3C2. The XRD test results show that the 1D / 2D CuZnCdS / Ti3C2 composite photocatalyst has been successfully prepared.

[0043] Figure 2 The scanning electron microscope image and EDS elemental analysis image of the 1D / 2D CZCS / TC prepared in Example 2, wherein: Figure 2 a is a scanning electron microscope image of 1D CuZnCdS prepared in Comparative Example 1, Figure 2 b is the scanning electron microscope image of 2D Ti3C2 prepared in comparative example 2, Figure 2 c is the SEM image of 1D / 2D CZCS / TC prepared in Example 2, Figure 2 d- Figure 2 i is the elemental analysis diagram. It can be seen that pure 1D CuZnCdS is a one-dimensional nanoparticle with a diameter of about 15-20nm, while 2D Ti3C2 presents an accordion-like layered two-dimensional structure. The electron microscope image of 1D / 2D CZCS / TC shows that 1D CuZnCdS is successfully grown on the surface of two-dimensional Ti3C2. In addition, during the in-situ growth process, the morphology and structure of 1D CuZnCdS and 2D Ti3C2 did not change. The close combination of 1D CuZnCdS and 2DTi3C2 helps to expose more active sites for photocatalytic reactions. More importantly, when photochemical reactions occur, 2D Ti3C2 promotes the photogenerated electron transfer rate of 1D CuZnCdS, thereby promoting the photocatalytic hydrogen production process. The elemental analysis spectrum of 1D / 2DCZCS / TC further confirms the presence and uniform distribution of all constituent elements Ti, C, Cu, Zn, Cd and S.

[0044] Figure 3 X-ray photoelectron spectrum of 1D / 2D CZCS / TC prepared in Example 2, wherein: Figure 3 a is the C1s spectrum, and it can be seen that the peaks at 281.8 eV, 286.5 eV, 284.9 eV, and 288.9 eV belong to C-Ti, CO, CC, and CF bonds, respectively; Figure 3 b is the Ti 2p spectrum, in which the peaks at 455.0 eV, 459.2 eV, 461.3 eV and 465.0 eV represent Ti-C 2p 3 / 2 、Ti-O2p 3 / 2 、Ti-C 2p 1 / 2 and Ti-O 2p 1 / 2 ; Figure 3 c is the Cu 2p spectrum, showing that the two peaks at 932.3 and 952.2 eV belong to Cu 2p 3 / 2 and Cu 2p 1 / 2 This indicates that copper exists in a divalent state in 1D CuZnCdS; Figure 3d is the Zn 2p spectrum, showing two peaks at 1021.9 and 1044.9 eV, corresponding to Zn 2+ Zn 2p 3 / 2 and Zn 2p 1 / 2 ; Figure 3 e is the Cd 3d spectrum. The peaks at 405.2 and 411.9 eV are respectively from the Cd 3d 5 / 2 and Cd 3d 3 / 2 These peaks are related to Cd 2+ related; Figure 3 f is the S2p spectrum. In 1D CuZnCdS, the peaks at 161.5 and 162.7 eV are S2p 3 / 2 and S2p 1 / 2 , S exists in the -2 valence state. In this composite material, the characteristic peaks at the same position are clearly visible, which means that the 1D / 2DCZCS / TC composite photocatalyst was successfully prepared. This result corroborates the structure measured by SEM. Compared with pure 2D Ti3C2, the characteristic peaks of C1s and Ti 2p in the 1D / 2DCZCS / TC composite photocatalyst both move toward the low energy level, which strongly proves that 2DTi3C2 plays an important role in promoting the migration of photogenerated electrons, thereby improving the hydrogen production performance.

[0045] Figure 4 The UV-visible diffuse reflectance spectrum and band structure of the 1D / 2D CZCS / TC prepared in Example 2, wherein: Figure 4 a is the UV-visible absorption spectra of 1D CuZnCdS, 2D Ti3C2 and 1D / 2D CZCS / TC composite photocatalyst materials. Figure 4 b is the band gap diagram of 1D CuZnCdS. Figure 4 c is the XPS-VB spectrum of 1D CuZnCdS material. Figure 4 d is the band structure diagram of CuZnCdS material.

[0046] like Figure 4 As shown in a, 1D CuZnCdS has a strong light absorption ability in the UV-visible light range (400-800), and the absorption edge is about 530nm. In addition, compared with 1D CuZnCdS, the 1D / 2D CZCS / TC composite photocatalyst has a stronger visible light absorption ability. This shows that loading 1D CuZnCdS nanoparticles on the surface of 2D Ti3C2 nanosheets is beneficial to improve the absorption of visible light. The band gap energy (E g ) can be inferred from the following formula:

[0047] (αhv) 1 / n =A(hv-Eg )

[0048] Where A is the proportionality constant, ν is the incident photon frequency, hν is the photon energy, α is the absorption coefficient, h is Planck's constant, and E g is the band gap energy of the sample (the band gap energy of an indirect gap semiconductor is n=1 / 2, and the band gap energy of a direct gap semiconductor is n=2). Figure 4 b shows that the band gap of 1D CuZnCdS is about 2.46 eV. XPS-VB technology detected the valence band (VB) spectrum of 1D CuZnCdS. Figure 4 c, the valence band potential is +1.76eV. The valence band spectrum of 1D CuZnCdS was detected by XPS-VB technology:

[0049] E VB =(E CB +E g )

[0050] Therefore, the VB position of 1D CuZnCdS is +1.76 eV (relative to NHE), and the CB position is +0.70 eV (relative to NHE). Figure 4 d shows the band structure of 1D CuZnCdS.

[0051] Figure 5 The electrochemical impedance spectroscopy, transient photocurrent, photoluminescence spectrum and time-resolved photoluminescence spectrum of the 1D / 2D CZCS / TC prepared in Example 2 are shown in FIG. Figure 5 a is the electrochemical impedance spectrum. As shown in the figure, in the Nyquist plot, the semicircle diameter on the surface of the 1D / 2D CZCS / TC composite photocatalyst is smaller than that of pure 1D CuZnCdS, which indicates that the 1D / 2D CZCS / TC composite photocatalyst has lower charge transfer resistance and better photoelectron-hole separation efficiency; Figure 5 b is the transient photocurrent test result, which shows the transient photocurrent of 1D CuZnCdS and 1D / 2D CZCS / TC composite photocatalysts. It can be seen that compared with 1D CuZnCdS, the photocurrent response of 1D / 2D CZCS / TC composite photocatalyst is higher, which indicates that the photogenerated charge carriers generated by 1D / 2D CZCS / TC composite photocatalyst have better charge separation ability and longer life. In order to analyze the charge carrier dynamics of the samples more deeply, we conducted photoluminescence (PL) and time-resolved photoluminescence (TRPL) tests on 1D CuZnCdS and 1D / 2D CZCS / TC composite photocatalysts. Generally speaking, the fluorescence intensity of the sample is inversely proportional to the free electron separation efficiency. Figure 5c is the photoluminescence spectrum. It can be seen that the PL signal intensity of the 1D / 2D CZCS / TC composite photocatalyst is much smaller than that of 1D CuZnCdS, which indicates that the 1D / 2D CZCS / TC composite photocatalyst accelerates the separation of photoexcited electrons and holes. Figure 5 d is the time-resolved photoluminescence (TRPL) spectrum, which shows that the average lifetime of the 1D / 2D CZCS / TC composite photocatalyst reaches 6.82ns, which is longer than that of 1D CuZnCdS (4.30ns). The 1D / 2D CZCS / TC composite photocatalyst improves the separation efficiency of photoinduced electron-hole pairs, thereby improving the photocatalytic activity.

[0052] The photocatalytic performance of 1D / 2D CZCS / TC prepared in Example 2, 1D CuZnCdS prepared in Comparative Example 1, and 2D Ti3C2 prepared in Comparative Example 2 was tested. The test method was: using a light power density of 1000 mW·cm -2 A 300W xenon lamp was used as the light source. 0.008 g of photocatalyst and 50 ml of a solution prepared by 0.25 M sodium sulfite, 0.35 M sodium sulfide and deionized water were added to a double-port quartz glass reactor. The mixture was stirred magnetically at 3000 rpm. The test was carried out in a cycle of 5 hours. At the end of each cycle, 0.25 M sodium sulfite and 0.35 M sodium sulfide were added again before the next cycle. HER was analyzed using a GC-7920 gas chromatograph (both the xenon lamp and the gas chromatograph were from Beijing Zhongjiao Jinyuan Technology Co., Ltd.). Before the test, the air in the reactor was completely removed to avoid interfering with the measurement value of hydrogen.

[0053] Figure 6 The photocatalytic performance, apparent quantum efficiency and stability test results of the 1D / 2D CZCS / TC prepared in Example 2, wherein: Figure 6 a is the test results of photocatalytic H2 production (5 hours) of 1D / 2D CZCS / TC, 1D CuZnCdS and 2D Ti3C2. Figure 6 b is the test results of hydrogen production rate of 1D / 2D CZCS / TC, 1D CuZnCdS and 2D Ti3C2. Figure 6 c is the apparent quantum efficiency of 1D / 2DCZCS / TC at different light wavelengths, Figure 6 d is the cyclic stability test result of hydrogen production by 1D / 2DCZCS / TC.

[0054] like Figure 6 a and Figure 6As shown in b, 2D Ti3C2 does not have redox ability, so hydrogen photocatalysis has not been tested using 2D Ti3C2 in the laboratory. The original 1D CuZnCdS has a hydrogen evolution rate (HER) of only 0.022 mol·g -1 ·h -1 However, after modification with 2D Ti3C2, the performance of photocatalytic hydrogen production was greatly improved. Figure 6 The apparent quantum efficiency (AQE) of the 1D / 2DCZCS / TC composite photocatalyst in c is consistent with the UV-visible absorption spectrum. The apparent quantum efficiency values ​​of the 1D / 2DCZCS / TC composite photocatalyst at 365nm and 420nm wavelengths are 3.05% and 0.61%, respectively. Figure 6 In d, the 1D / 2DCZCS / TC composite photocatalyst can still maintain 91% of its catalytic activity after 15 hours of photocatalytic experiment, which proves that the 1D / 2DCZCS / TC composite photocatalyst has good catalytic stability.

[0055] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above embodiments, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a sulfur-cadmium-zinc-copper based composite photocatalyst, characterized in that: The steps include: (1) adding zinc acetate dihydrate, cadmium acetate dihydrate, and copper nitrate trihydrate to deionized water, mixing them evenly, adding sodium sulfide nonahydrate and stirring to dissolve, and then adding titanium carbide and mixing them evenly to obtain a mixed solution; (2) The mixed solution obtained in step (1) is transferred into a stainless steel reactor with a polytetrafluoroethylene liner, and then placed in an oven for reaction. After the reaction is completed, the reaction product is centrifuged and washed, and the solid product is collected and dried to obtain a sulfur-cadmium-zinc-copper based composite photocatalyst.

2. The method for preparing the sulfur-cadmium-zinc-copper based composite photocatalyst according to claim 1, characterized in that: In step (1), the mass ratio of zinc acetate dihydrate, cadmium acetate dihydrate, copper nitrate trihydrate, sodium sulfide nonahydrate and titanium carbide is (0.05-1): (0.1-1.5): (0.01-0.2): (0.4-1): (0.01-0.3).

3. The method for preparing the sulfur-cadmium-zinc-copper based composite photocatalyst according to claim 1, characterized in that: In step (2), the reaction temperature is 140-180° C. and the reaction time is 2-6 hours.

4. The method for preparing the sulfur-cadmium-zinc-copper based composite photocatalyst according to claim 1, characterized in that: In step (2), the number of centrifugal washing is 2 to 4 times.

5. The method for preparing the sulfur-cadmium-zinc-copper based composite photocatalyst according to any one of claims 1 to 4, characterized in that: In step (2), the drying temperature is 60 to 70° C. and the drying time is 10 to 20 hours.

6. Use of the sulfur-cadmium-zinc-copper based composite photocatalyst prepared by the method according to any one of claims 1 to 5 in the photocatalytic decomposition of water to produce hydrogen.